Mediation Effects of Subjective Norms on the Relationship between Career Advancement and Job Characteristics and Knowledge Sharing Behavior among the Tanzanian Healthcare Professionals - Mohamed Abbasi Balozi; Siti Zubaidah Othman; Mohd Faizal Mohd Isa (Gadjah Mada International Journal of Business, 2018)
This paper intends to examine the mediating effects of subjective norms on the relationship between career advancement and job characteristics and knowledge sharing behavior. Based on the social exchange theory, we establish a research model which contains job and organizational factors. We distributed 650 questionnaires, but only 439 questionnaires were returned and usable. The hypotheses were tested using Partial Least Squares Structural Equation Modeling (PLS-SEM). The study examines knowledge sharing behavior and its determinants. The results reveal that career advancement, job characteristics and subjective norms are positively and significantly related to knowledge sharing behavior. The findings depict that subjective norms have a partial positive and significant mediating effect on knowledge sharing behavior. This paper intends to identify knowledge sharing behavior and its determinants in Tanzanian healthcare institutions and among healthcare professionals. This is because there are only a few such studies in the context of Tanzania; therefore, this study offers a theoretical foundation for future studies and practical implications for administrators and practitioners.